Reinforcement of polypropylene with lignocellulose nanofibrils and compatibilization with biobased polymers. Issue 34 (18th May 2016) - Ferrer, Ana; Hoeger, Ingrid C.; Lu, Xiaomin; Rojas, Orlando J.
ABSTRACT: Freeze‐dried and milled lignocellulose nanofibrils (LCNF) were used to reinforce polypropylene (PP) nanocomposites. The LCNF, containing up to 9% lignin, was obtained from residual Empty Palm Fruit Bunch (EPFB) fibers. Soy protein isolate (SPI) and hydroxypropyl cellulose (HPC) were tested as coupling agents as well as maleic anhydride grafted polypropylene (MAPP), which was used as a reference. A good level of dispersion of LCNF in the PP matrix while mechanical testing and thermal analyses indicated an improvement of the thermo‐mechanical behavior of the nanocomposites was revealed upon loading of the lignin‐containing nanofibrils. The tensile modulus of PP was increased by 15% upon the addition of 1% LCNF with SPI as a compatibilizer. Likewise, the thermal stability of the composites was most markedly enhanced. Overall, LCNF and SPI, two important bioresources, are introduced here for the development of novel and cost‐effective PP‐based composites. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 43854. Abstract :